Accurate and quick predictor of necrotizing soft tissue infection: Usefulness of the LRINEC score and NSTI assessment score. Issue 4 (April 2020) - Harasawa, Tomofumi; Kawai-Kowase, Keiko; Tamura, Jun'ichi; Nakamura, Mitsunobu
Abstract: Objective: The Laboratory Risk Indicator for Necrotizing Fasciitis (LRINEC) score is a diagnostic tool for necrotizing soft tissue infection (NSTI), which is validated and is considered to have high diagnostic value. However, some experts criticize LRINEC score for consisting of laboratory test results only. Methods: In this single-center retrospective study, we created a new scoring system (NSTI assessment score; NAS), which also incorporated vital signs as another diagnostic tool for NSTI using cases from our hospital and also evaluated diagnostic accuracy of LRINEC score. We identified NSTI predictors by comparing 24 NSTI patients and 80 non NSTI patients using uni- and multivariate logistic regression analysis, and created NAS based on odds ratio of variables which are statistically significant in the multivariate model. Results: We identified mean arterial pressure, C-reactive protein, hemoglobin, serum creatinine, and glucose as a predictor for NSTI. The maximum value of NAS was 11 points with the cut-off value of 6. Sensitivity, specificity, positive predictive value, and negative predictive value of the NAS for diagnosis of NSTI were 87.5%, 91.3%, 75.0%, and 96.1%, respectively. Area under the receiver operating characteristic curve was 0.926 (0.851–1.00) for the NAS and 0.903 (0.833–0.973) for the LRINEC score, and they were not statistically different (p = 0.167). Conclusion: The NAS has high diagnostic accuracy in predicting NSTI, and is comparable with the LRINEC score. The NAS needs to be validated in other cohorts in the future.